Effect of Installation of Solar Collector on Performance of Balcony Split Type Solar Water Heaters. (31st December 2015) - Ji, Xu; Li, Ming; Lin, Weidong; Zheng, Tufeng; Wang, Yunfeng
Abstract : The influences of surface orientation and slope of solar collectors on solar radiation collection of balcony split type solar water heaters for six cities in China were analyzed by employing software TRNSYS. The surface azimuth had greater effect on solar radiation collection in high latitude regions. For deviation of the surface slope angle within ±20° around the optimized angle, the variation of the total annual collecting solar radiation was less than 5%. However, with deviation of 70° to 90°, the variation was up to 20%. The effects of water cycle mode, reverse slope placement of solar collector, and water tank installation height on system efficiency were experimentally studied. The thermal efficiencies of solar water heater with single row horizontal arrangement all-glass evacuated tubular collector were higher than those with vertical arrangement at the fixed surface slope angle of 90°. Compared with solar water heaters with flat-plate collector under natural circulation, the system thermal efficiency was raised up to 63% under forced circulation. For collector at reverse slope placement, the temperature-based water stratification in water tank deteriorated, and thus the thermal efficiency became low. For improving the system efficiency, an appropriate installation height of the water tank was suggested.